2014
DOI: 10.1007/s00441-014-1848-2
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses and neuroepithelial degeneration and regeneration in the mouse olfactory mucosa induced by intranasal administration of Poly(I:C)

Abstract: The pathogenesis of postviral olfactory disorder (PVOD) has not been fully elucidated. We investigated morphological changes and innate immune responses in the mouse olfactory mucosa induced by intranasal administration of polyinosinic-polycytidylic acid [Poly(I:C)], a synthetic analog of viral double-stranded RNA. Mice received three administrations of saline with or without Poly(I:C), once every 24 h. The olfactory mucosa was harvested at various intervals after the first administration (8 h, 3, 9 and 24 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 68 publications
(77 reference statements)
2
71
0
Order By: Relevance
“…Olfactory loss in rhinitis/sinusitis is attributable primarily to blockade of airflow to the olfactory sensory neurons (OSNs) that receive odorous molecules, but damage to the OM is also considered as a possible cause (2, 46). In fact, multiple studies have shown that olfactory inflammation causes the loss of OSNs (714). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory loss in rhinitis/sinusitis is attributable primarily to blockade of airflow to the olfactory sensory neurons (OSNs) that receive odorous molecules, but damage to the OM is also considered as a possible cause (2, 46). In fact, multiple studies have shown that olfactory inflammation causes the loss of OSNs (714). …”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, believe that a better understanding of the olfactory immune system will advance our knowledge of the pathogenesis and progression of neurological disease. To date, there are many reports showing that artificially induced olfactory inflammation can cause immune responses and damage to the OM (714). Conversely, new OSNs are generated in the OM throughout life, which may help in the repair of damaged tissue (30, 31).…”
Section: Introductionmentioning
confidence: 99%
“…The dose of poly(I:C) used was determined from the doses used in previous studies of respiratory mucosa [24,25] . The control rats received saline alone in the same manner (this experimental group was designated as the CON or IgAN group).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Lysates of cultured cells were prepared as previously described [24] . After centrifugation, the protein level was determined in supernatants using a micro BCA protein assay kit with bovine serum albumin as a standard (Pierce, Thermo).…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation